Adult Education, Stratification, and Regime Change: Upgrading and Sidestepping in Russia, 1965–2005. Issue 2 (April 2019) - Kosyakova, Yuliya; Gerber, Theodore P.
Adult education influences how labor market opportunities are structured in the later life course. We propose a theoretical framework for understanding the stratifying role of adult education resting on the distinction between two forms of adult education—upgrading and sidestepping: Resources, incentives, and selection processes systematically structure rates of participation. Using educational history data from Russia, we test hypotheses derived from our framework and examine the impact of the Soviet collapse and the ensuing economic recovery. Upgrading exacerbates patterns of socioeconomic stratification by delivering better credentials to individuals with higher levels of initial resources. Sidestepping is less common than upgrading and less related to socioeconomic origins and previous attainment. The Soviet collapse produced short-term declines in the rates of both upgrading and sidestepping. However, once growth resumed, market institutions proved durable, and the political regime stabilized, rates of upgrading soared to levels exceeding those of the Soviet era.